Letter (copy) : Spanish refugee metalworkers - Tewson, Vincent
026-0012-001 INTERNATIONAL. EAB. 22nd August 1939. Mr. W. Carrillo, 7, Orme Court, Bayswater Road, LONDON. W. 2. Dear Comrade Carrillo, SPANISH REFUGEE METALWORKERS. In the absence of Sir Walter Citrine on holiday, I am replying to your letter of the 16th August regarding the position which has arisen in France in connection with the employment of Spanish refugees in the metal industry. I am sending a copy of your letter to Mr. Schevenels, General Secretary of the International Federation of Trade Unions, and no doubt Sir Walter Citrine will communicate with you again on the matter when he returns to the office. Yours sincerely, Assistant Secretary. 292/946/26/12